Fluid and carbohydrate replacement during exercise: How much and why? - Coyle, E. E. (Sports Science Exchange, 1994)
The purpose of this paper is to review the physiology of fluid and carbohydrate replacement during exercise and the likely effects of such replacement on the performance of pro-longed exercise. It is hoped that this knowledge might encourage competitors to drink more during exercise.